The Influence of the Project Based Learning Model to Improve Students' Creative Thinking Skills in IPAS Subjects in Class IV of UPTD SD Negeri 124401 Pematangsiantar - Saragih, Jihan Nurhadillah; Thesalonika, Emelda; Siagian, Asister Fernando (PT. Anagata Sembagi Education, 2025)
This study aims to determine the effect of the Project Based Learning model on improving students' creative thinking skills in the Natural Sciences subject with the material